The Validity of Problem-Based Contextual Model in the History Learning at Senior High School - Siti Aisyah; Heri Effendi; Joni Indra Wandi; Salman M Noer; Cipto Duwi Priyono (Indonesia Approach Education, 2023)
Learning models can improve the quality of education. Therefore, this paper aims to prove the validity level of the problem-based contextual model in learning history through selected documentary films. This research refers to research and development. The process was used to produce and validate a product including educational products. The resulting educational product is a problem-based contextual learning model in learning history, which used ADDIE design model. The problem-based contextual model in history learning in high school is in the valid category. This model is a new learning model developed from the contextual learning model. Documentary film is one of the tools that can be used as a medium to deliver learning material. Visualization in film can make the expected atmosphere really felt and as if students are participating in the conditions in the film. In this case, the teacher has the essential role in explaining important points that become the subject of discussion so that learning a history will be more dynamic and varied. The problem-based contextual model was developed based on theoretical studies of learning theories, and also of learning values ​​to develop attitudes. The learning is based on student oriented. The problem-based contextual model consists of six syntaxes, namely: Visualization Problem, Relating, Experience, Applying, Cooperating Transferring, and Clarification.